Krasnova A.N. Hydrophilic genus Rogoz (Typha L.) (within the former USSR). - Yaroslavl: "Printhouse-Yaroslavl", 2011. -186 p. Fig. 33. Bibliography: ISBN 978-5-904234-21-8. (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Krasnova A.N. Hydrophilic genus Rogoz (Typha L.) (within the former USSR). - Yaroslavl: "Printhouse-Yaroslavl", 2011. -186 p. Fig. 33. Bibliography: ISBN 978-5-904234-21-8.